Preparation and characterization of Bis-GMA free dental resin system with synthesized dimethacrylate monomer TDDMMA derived from tricyclo[5.2.1.0(2, 6)]-decanedimethanol. (April 2016) - Yin, Mei; Liu, Fang; He, Jingwei
Abstract: As a substitute for 2, 2-bis[4-(2-hydroxy-3- methacryloxypropoxy)phenyl] propane (Bis-GMA) in dental materials, a new dimethacrylate monomer TDDMMA without bisphenol-A structure was synthesized through the reaction between tricyclo[5.2.1.0(2, 6)]- decanedimethanol and 2-isocyanatoethyl methacrylate. The TDDMMA was mixed with triethylene glycol dimethacrylate (TEGDMA) to prepare Bis-GMA free dental resin. Physicochemical properties, such as double bond conversion (DC), polymerization shrinkage (VS), water sorption (WS) and solubility (SL), flexural strength (FS) and modulus (FM) and fracture energy of TDDMMA/TEGDMA resin system were investigated. Bis-GMA/TEGDMA resin system was used as a control. The results showed that, compared with Bis-GMA/TEGDMA resin system, TDDMMA/TEGDMA resin system had comparable VS and several advantages like higher DC, lower SL and better mechanical properties after water immersion. Highlights: A new bisphenol-A free dimethacrylate monomer TDDMMA was synthesized. Bis-GMA free dental resin was prepared with TDDMMA as base resin. TDDMMA based resin had comparable shrinkage as Bis-GMA based resin. TDDMMA based resin had several advantages when compared with Bis-GMA based resin.